2022
DOI: 10.3390/joitmc8030139
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Development of Circular Systems While Ensuring Economic Security in the Industry

Abstract: This article is devoted to the formation of methodological foundations of the circular economy on the safety of industrial enterprises. The dependence of the system of economic security from the circular economy concept is implemented by the 3 R model. The model is based on the consistency of quantitative, value and normative indicators. These indicators together allow a comprehensive analysis of the dynamics and direction of the process of implementation of technologies of circular use of resources. The main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…The most time-consuming process of countering the spread of harmful information in social networks from the point of view of efficiency is the operator's working time, respectively, at the stage of setting up the system and at the stage of operation. The experts evaluated the following tasks: the time needed by the operator to identify information threats, their signs (the expert fills in a table with three threats and their signs); the time the operator spends on choosing the appropriate available implementation agents and countermeasures (the expert fills in the table with available implementation agents and countermeasures; time required by the operator to fulfill the request for collection, analysis of information; time spent by the operator on selecting informational objects of influence and adjusting relevant pairs, targetcountermeasure [23]. Thus, on the basis of the conducted research, the time characteristics of the operator's work at the stage of setting up the system and at the stage of operation of the system of countering the spread and detection of harmful information in social networks were obtained.…”
Section: Evaluation Of the Methods Of Countering The Spread And Detec...mentioning
confidence: 99%
“…The most time-consuming process of countering the spread of harmful information in social networks from the point of view of efficiency is the operator's working time, respectively, at the stage of setting up the system and at the stage of operation. The experts evaluated the following tasks: the time needed by the operator to identify information threats, their signs (the expert fills in a table with three threats and their signs); the time the operator spends on choosing the appropriate available implementation agents and countermeasures (the expert fills in the table with available implementation agents and countermeasures; time required by the operator to fulfill the request for collection, analysis of information; time spent by the operator on selecting informational objects of influence and adjusting relevant pairs, targetcountermeasure [23]. Thus, on the basis of the conducted research, the time characteristics of the operator's work at the stage of setting up the system and at the stage of operation of the system of countering the spread and detection of harmful information in social networks were obtained.…”
Section: Evaluation Of the Methods Of Countering The Spread And Detec...mentioning
confidence: 99%
“…increasing the innovative and intellectual potential of the enterprise; use of world-leading experience in managing material, labor and financial resources of the enterprise; improving According to scientists Kuzior A. et al (2022), the assessment of the impact of the circular economy concept on the economic security system of industrial enterprises allows us to ascertain the monopoly of certain industries. The authors identified resource availability, secondary use of materials and results as the main factors influencing the circular economy concept on the safety of industrial enterprises.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Формування захисту керівництва та персоналу організації встановлюються і регулюються положенням (інструкцією), що затверджується керівником організації, і в окремих випадках погоджується з територіальними органами внутрішніх справ і органами безпеки [2].…”
Section: механIзм регулювання економIкиunclassified